PROBLEMATIKA PENGKADERAN DI PERGURUAN TINGGI MUHAMMADIYAH MATARAM DALAM PERSPEKTIF NORMA PENGKADERAN MUHAMMADIYAH - Mappanyompa Mappanyompa; Imawanto Imawanto (Universitas Muhammadiyah Mataram, 2019)
This article discusses the problem of cadre formation in Muhammadiyah Mataram universities in the perspective of cadre norms. In full, cadres are those who have been completed in following all formal cadres, tested in informal cadres and have provisions through informal formation. Their existence is not only expected in the existence of the organization to be maintained, but also expected that the cadres will continue to carry out the mission of the organization's movement to the full. This type of research is quantitative explanatory research, with data collection techniques through library research and field work research. The results of the study show that regeneration occupies a very strategic position for the survival of Muhammadiyah as a community and Islamic missionary movement Amar Ma'ruf Nahi Munkar. Cadreization must be of serious concern from all Muhammadiyah leaders and Muhammadiyah's charitable business leaders, especially in West Nusa Tenggara. The foundation of sincere intention to live Muhammadiyah and not only seek life in the Muhammadiyah as the message of the founder of the late KH. Ahmad Dahlan. The origins of the Kemuhammadiyahan strategic position holder in the Muhammadiyah charity business must be directly proportional to the cadre process that has been traversed on the basis of commitment and the complete and complete cadre norm.Keywords: cadre norms; cadre problems; Muhammadiyah universities.Artikel ini membahas tentang problematika pengkaderan di Perguruan Tinggi Muhammadiyah Mataram perspektif norma pengkaderan. Secara utuh kader adalah mereka yang telah tuntas dalam mengikuti seluruh pengkaderan formal, teruji dalam pengkaderan informal dan memiliki bekal melalui pengkaderan non formal. Keberadaan mereka bukan saja diharapkan dalam eksistensi organisasi tetap terjaga, melainkan juga diharapkan kader tetap akan membawa misi gerakan organisasi hingga paripurna. Jenis penelitian ini adalah penelitian eksplanatif kuantitatif, dengan teknik pengumpulan data melalui library research dan field work research. Hasil penelitian menunjukkan bahwa kaderisasi menempati posisi yang sangat strategis bagi kelangsungan hidup Muhammadiyah sebagai sebuah persyarikatan dan gerakan Islam dakwah amar ma'ruf nahi munkar. Kaderisasi menjadi perhatian yang sungguh-sungguh dari segenap pimpinan Muhammadiyah dan pimpinan amal usaha Muhammadiyah, terutama di Nusa Tenggara Barat. Landasan niat yang tulus untuk menghidup-hidupkan Muhammadiyah dan tidak semata mencari hidup dalam Muhammadiyah sebagaimana pesan sang pendirinya almarhum KH. Ahmad Dahlan. Asal-usul kemuhammadiyahan pemegang jabatan strategis di amal usaha Muhammadiyah harus berbanding lurus dengan proses pengkaderan yang telah dilalui atas dasar komitment dan norma pengkaderan secara tuntas dan paripurna.Kata kunci: norma pengkaderan; perguruan tinggi Muhammadiyah; problematika pengkaderan.